PENGARUH KOORDINASI OLEH KEPALA DINAS TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN MAJALENGKA - Ratna S.IP., M.Si. (Jurnal Ilmu Administrasi CENDEKIA, 2017)
ABSTRACTThe work effectiveness condition is still not significant, it can be seen from several indicators that there are still employees who finish the work not on time, there are still employees who have not provided maximum results, there are still employees who lack innovation in the execution of work. The reason is allegedly because the Head of Service has not been optimal in supervising the implementation of work, allegedly the Head of Service has not been optimal in carrying out scheduled coordination. The research method used is quantitative descriptive method. The population in this study were 30 people with a sample of 28 people with a 5% error level using the Slovin formula. Data collection techniques are observation and questionnaires or questionnaires to research respondents. While the data processing in this study uses the SPSS Statistics 20.0 program. The results of the analysis and discussion obtained through observation and questionnaire can be concluded that the coordination carried out by the Head of Service has not been fully optimal so that it influences the low effectiveness of the work of employees in the One Door Investment Services and Integrated Services of Majalengka Regency. From the results of the analysis shows that the coordination of the Head of Office on the work effectiveness of employees there is a significant influence that is where rcount is greater than rtable or 0.891 > 0.374. The coefficient of determination (R2) is 79.4% meaning that the work effectiveness of employees is influenced by the coordination of the Head Office and 20.6% is influenced by other factors and not examined. But it is expected that the One-Stop Integrated Investment and Services Office of Majalengka Regency in this case the Head of Service or top management in order to further improve coordination so that the level of work effectiveness of employees is more optimal and so as to facilitate the achievement of organizational goals. Keywords: Coordination, Employee Effectiveness ABSTRAKKondisi efektivitas kerja masih belum optimal, hal ini terlihat dari beberapa indikator yaitu masih ada pegawai yang menyelesaikan pekerjaan tidak tepat waktu, masih ada pegawai yang belum memberikan hasil yang maksimal, masih ada pegawai yang kurang inovasi dalam pelaksanaan pekerjaan. Penyebabnya adalah diduga karena Kepala Dinas belum optimal dalam mengawasi pelaksanaan kerja, diduga Kepala Dinas belum optimal dalam melaksanakan koordinasi secara terjadwal. Metode penelitian yang digunakan adalah metode deskriptif kuantitatif. Populasi dalam penelitian ini sebanyak 30 orang dengan sampel 28 orang dengan taraf kesalahan 5% menggunakan rumus slovin. Teknik pengumpulan data yaitu dengan observasi dan penyebaran angket atau kuisioner kepada responden penelitian. Sedangkan pengolahan data dalam penelitian ini menggunakan program SPSS Statistics 20.0. Hasil analisis dan pembahasan yang diperoleh melalui observasi dan kuisioner dapat disimpulkan bahwa koordinasi yang dilakukan oleh Kepala Dinas belum sepenuhnya optimal sehingga berpengaruh terhadap rendahnya efektivitas kerja pegawai pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Majalengka. Dari hasil analisis menunjukkan bahwa koordinasi Kepala Dinas terhadap efektivitas kerja pegawai terdapat pengaruh yang signifikan yaitu dimana rhitung lebih besar daripada rtabel atau 0,891 > 0,374. Koefisien determinasi (R2) yaitu 79,4% artinya efektivitas kerja pegawai dipengaruhi oleh koordinasi Kepala Dinas dan 20,6% dipengaruhi faktor lain dan tidak diteliti. Tetapi diharapkan kepada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Majalengka dalam hal ini Kepala Dinas atau pucuk pimpinan supaya lebih meningkatkan koordinasi sehingga tingkat efektivitas kerja pegawai lebih optimal serta supaya dapat mempermudah dalam pencapaian tujuan organisasi. Kata Kunci: Koordinasi, Efektivitas Kerja